2002
DOI: 10.1038/sj.leu.2402467
|View full text |Cite
|
Sign up to set email alerts
|

B-CLL cells are capable of synthesis and secretion of both pro- and anti-angiogenic molecules

Abstract: Initial work has shown that clonal B cells from B-chronic lymphocytic leukemia (B-CLL) are able to synthesize pro-angiogenic molecules. In this study, our goal was to study the spectrum of angiogenic factors and receptors expressed in the CLL B cell. We used ELISA assays to determine the levels of basic fibroblast growth factors (bFGF), vascular endothelial growth factor (VEGF), endostatin, interferon-␣ (IFN-␣) and thrombospondin-1 (TSP-1) secreted into culture medium by purified CLL B cells. These data demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 62 publications
5
94
0
2
Order By: Relevance
“…As CLL cells themselves produce VEGF, 6 VEGFR stimulation can occur in an autocrine fashion. 8 Moreover, CLL cells expressing VEGFR-2 and higher levels of VEGF in patients' serum correlate with shortened survival. 33 Importantly, no activating mutations in VEGFRs have been described in CLL, indicating that survival effects depend on VEGF binding to the receptor rather than being ligand To induce CLL proliferation, cells were stimulated with DSP30 (100 U/ml) and interleukin (IL)-2 as described elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As CLL cells themselves produce VEGF, 6 VEGFR stimulation can occur in an autocrine fashion. 8 Moreover, CLL cells expressing VEGFR-2 and higher levels of VEGF in patients' serum correlate with shortened survival. 33 Importantly, no activating mutations in VEGFRs have been described in CLL, indicating that survival effects depend on VEGF binding to the receptor rather than being ligand To induce CLL proliferation, cells were stimulated with DSP30 (100 U/ml) and interleukin (IL)-2 as described elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CLL cells not only are capable of producing VEGF, 6 but VEGFRs were also found to be expressed on the surface of leukemic cells. [7][8][9] These observations have led to the hypothesis that the apoptosis defect of CLL cells is partly mediated through an autocrine feedback loop involving VEGF. 8 Sorafenib (BAY43-9006; Nexavar) is an oral multikinase inhibitor approved for the treatment of patients with advanced renal cell carcinoma 10 and those with unresectable hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,29 Although a causal relationship remains to be established, it is thus possible that the observed inhibition of MMP-9 production might result from HF-elicited VEGF downregulation. Indeed, due to the fact that B-CLL cells express VEGF receptors functionally active in angiogenesis, 29,30 the hypothesis of an autocrine loop of VEGF has to be considered in B-CLL, 31 and moreover, an autocrine stimulation of VEGFR-2 has been described to induce MMP-9 expression as well as cell growth and migration in some leukaemia. 32 Furthermore, elevated MMP-9 levels are also produced in the plasma of adult T-cell leukemia (ATL) patients; they are closely related to high VEGF levels and are significantly associated with strong ATL cell infiltration, suggesting that MMP-9 and VEGF could cooperate in invasion processes.…”
Section: Discussionmentioning
confidence: 99%
“…CLL cells themselves produce VEGF, 5,6 and high levels of this growth factor in serum, 7 as well as high expression of VEGF receptor (VEGFR)-2 on the malignant cells, 8 correlate with shortened patient survival. Moreover, in a previous study, 5 we observed increased vascularisation in enlarged lymph nodes of CLL patients and proposed that this was caused by paracrine stimulation of endothelial cells by CLL-cell-derived VEGF.…”
Section: Introductionmentioning
confidence: 99%